Morphological and genetic analysis of Sulawesi Rhacophorus and description of a fourth species endemic to the island - Hamidy, Amir; Riyanto, Awal; Munir, Misbahul; Gonggoli, Ade Damara; Trilaksono, Wahyu; Mcguire, Jimmy A. (Zootaxa, 2025)
A new species of tree frog of the genus Rhacophorus is described from two different localities on Sulawesi Island, Indonesia. The new species is divergent morphologically and genetically, and is deeply nested within the monophyletic group of endemic Sulawesian Rhacophorus comprising R. edentulus, R. georgii, and R. monticola. The new species has a combination of distinctive morphological characteristics that distinguishes it from other Rhacophorus species, including from other Sulawesian Rhacophorus: medium size SVL 40.4–44.6 mm in males; 48.1–54.2 mm in females, males have sloped snout in lateral view, presence of vomerine teeth, absence of a bony crest in the occipital region of the skull, dorsal skin coarsely granular with white-tipped keratinized asperities, flank with white blotched pattern, dermal flaps absent on limbs, heel without dermal appendage, and tuberculate cloaca. The discovery of the new species enhances knowledge of the diversity of endemic Sulawesian amphibians and requires future conservation efforts, especially in light of ongoing threats such as agricultural expansion.